Konsumsi Air Minum Dalam Kemasan (AMDK) Pada Mahasiswa - Dyah Suryani; Zahrul Mufrodi; Asep Rustiawan (Universitas Wiralodra, 2019)
The high consumption of bottled water contributes to environmental problems, including water waste and pollution. Environmental problems caused by plastic bottles, waste of drinking water because they are not drunk, soil pollution due to the presence of the water that cannot be decomposed. The purpose of this study was to determine the factors associated with consumption of Bottled Drinking Water (AMDK) in students in terms of practical, health and the environment. This study is an observational analytic study with a cross-sectional approach by conducting an online survey of students from a private university in the city of Yogyakarta to explore the factors associated with the consumption of bottled drinking water. Respondents (N = 156) taken randomly. The results of the study stated that students chose bottled water from the practical side not influenced by gender, study programs, the number of semesters taken, and the amount of pocket money. Consumption of bottled water for health reasons is influenced by the origin of the study program (p-value 0.041) and the number of semesters taken (p-value 0.002). The consumption of bottled water for environmental reasons is influenced by the number of semesters that have been taken (p-value 0.015) and the status of residence in Yogyakarta (p-value 0.035).